2016
DOI: 10.1111/1440-1681.12533
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bio‐distribution of novel super paramagnetic iron oxide nanoparticles (SPIONs) in the anaesthetized pig

Abstract: Manufactured nanomaterials have a variety of medical applications, including diagnosis and targeted treatment of cancer. A series of experiments were conducted to determine the pharmacokinetic, biodistribution and biocompatibility of two novel magnetic nanoparticles (MNPs) in the anaesthetized pig. Dimercaptosuccinic acid (DMSA) coated superparamagnetic iron oxide nanoparticles (MF66-labelled 12 nm, core nominal diameter and OD15 15 nm); at 0.5, or 2.0 mg/kg) were injected intravenously. Particles induced a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…In anaesthetized pigs, it has been demonstrated that dimercaptosuccinic acid coated superparamagnetic iron oxide nanoparticles (MF66-labelled 12 nm, core nominal diameter and OD15 15 nm); at 0.5, or 2.0 mg/kg injected i.v. induced a transient yet significant decrease in MAP [ 38 ]. Particles remained in the circulation for up to 30 min and were accumulated in the liver, spleen and lungs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In anaesthetized pigs, it has been demonstrated that dimercaptosuccinic acid coated superparamagnetic iron oxide nanoparticles (MF66-labelled 12 nm, core nominal diameter and OD15 15 nm); at 0.5, or 2.0 mg/kg injected i.v. induced a transient yet significant decrease in MAP [ 38 ]. Particles remained in the circulation for up to 30 min and were accumulated in the liver, spleen and lungs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that after 6 hours of injection >50% of iron is found in liver 79. These studies suggest the involvement of reticular endothelial system in the clearance of NPs and major problem in biomedical application of these particles 137. Higher vascularization and permeability of iron NPs are responsible for their uptake by reticular endothelial system140 and macrophage.…”
Section: Biodistribution and Bioelimination Of Iron Npsmentioning
confidence: 99%
“…Size, shape, and surface characterization of iron NPs determine their biological distribution135 and can involve opsonization (serum protein interaction) and particle cell interaction 136. Various biodistributation studies report blood, spleen, liver, and kidney as probable localization for the NPs, and preferentially accumulation occurs in liver and spleen 137. Recent studies report that ultrasmall iron oxide NPs can be used as potent MRI contrast agents 27,138.…”
Section: Biodistribution and Bioelimination Of Iron Npsmentioning
confidence: 99%
See 2 more Smart Citations